Boosting the acidic electrocatalytic nitrogen reduction performance of MoS2 by strain engineering. Issue 20 (18th May 2020) - Liang, Jiawei; Ma, Shuangxiu; Li, Jing; Wang, Yangang; Wu, Junli; Zhang, Quan; Liu, Zhao; Yang, Zehui; Qu, Konggang; Cai, Weiwei
Abstract : The interlayer space of MoS2 was compressed by substituted F ions for the purpose of rationally boosting the NRR activity and selectivity. Abstract : It has been widely confirmed that expanding the layer spacing of layer-structured MoS2 can boost the hydrogen evolution reaction (HER) activity of MoS2 . Inspired by this, a strain engineering strategy was applied to defect-rich MoS2 nanosheets by facilely substituting F to compress the interlayer space of MoS2 . Because of the smaller size and higher electronegativity of F as compared to S, the catalytic HER was remarkably suppressed. By considering the strongly reduced uphill energy for the hydrogenation of adsorbed N2 on MoS2 due to the introduction of F ions, as revealed by first-principles calculations, electrochemical nitrogen reduction reaction (NRR) activity and selectivity on the F-doped MoS2 (F-MoS2 ) catalyst under acidic conditions can be significantly boosted. Faradaic efficiency toward the NRR on F-MoS2 was therefore enhanced to 20.6% with a maximum NH3 yield of 35.7 μg h −1 mgcat −1 at −0.2 V vs. RHE during long-term operation.